Policy Variation, Labor Supply Elasticities, and a Structural Model of Retirement - Dayanand Manoli; Kathleen Mullen; Mathis Wagner (Institute for the Study of Labor (IZA), 2014)
This paper exploits a combination of policy variation from multiple pension reforms in Austria and administrative data from the Austrian Social Security Database. Using the policy changes for identification, we estimate social security wealth and accrual elasticities in individuals' retirement decisions. Next, we use these elasticities to estimate a dynamic programming model of retirement decisions. Finally, we use the estimated model to examine the labor supply and welfare consequences of potential social security reforms.
Keywords: J26; H55; 330; policy variation; retirement; labor supply elasticities